INTERNALIZATION OF RELIGIOUS CHARACTER THROUGH HALAQAH TARBIYAH: A STUDY OF STUDENT PERCEPTIONS AT AL-QUR'AN WAHDAH ISLAMIYAH HIGH SCHOOL - Samsuddin Samsuddin; Abdurrahman Abdurrahman; Aditia M Yusup (STAI Sebelas April Sumedang, 2025)
This study aims to examine students' perceptions of the effectiveness of the halaqah tarbiyah program in shaping religious character at SMA Al-Qur’an Wahdah Islamiyah. The topic was chosen due to the urgent need for character education based on Islamic values amid the growing moral challenges faced by the younger generation. The halaqah program, as a part of non-formal education in Islamic school settings, is viewed as a strategic means to foster comprehensive religious personality development. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and documentation involving students actively participating in the halaqah. The findings reveal that the halaqah is perceived as an effective developmental space, addressing students’ spiritual, emotional, and social dimensions. Four key themes emerged: enhanced spiritual awareness, internalization of Islamic moral values, habituation of worship, and the influence of a religious social environment. The program successfully integrates the principles of targhib (spiritual motivation), exemplary behavior of the murabbi, consistent practice of good deeds, and supportive peer interaction to encourage positive behavioral change. The halaqah not only delivers religious content but also practically and sustainably cultivates religious character. The study concludes that halaqah tarbiyah represents a relevant and contextual model for Islamic character education. It is recommended that such programs be developed systematically and considered as a reference for character-building policies in Islamic educational institutions. Keywords: Halaqah Tarbiyah, Religious Character, Islamic Education; Character Education